(3eLeY GdahGFO GdHOfjIs
(3ChdgG (B:s
(3adeG cGf cJGH GdeaQOGJ Gdeda eGdG jSY GdWHjH LgO Lgdg bdjd GdebOGQ , hLdGdJg HLdGd CUdg s
(3BNQgG (B:s
(3GdTH jfaY dQO GdeNGha hWQO GdYjf , JYdjbkG ai GdHGHhfL, TOjO ddfaY ai GdEYHGA eQhNkG , hjbY ai eQGgeI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B167 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI hdi GdOjf (B(2537) s
Keywords: (3GdWHs